La cultura docente en una escuela pública urbanomarginal de Lurin - Lima - Sánchez Huarcaya, Alex Oswaldo (2020)
In this research work the study of the teachers culture of a Public Educational Institution of the district of Lurín (Lima), based on the beliefs of the professors, is approached. The study considers the theoretical foundations of school culture by asking the following research question: How is the teaching culture from the beliefs of teachers in an I.E of Lurín? Based on the question, we propose the following objective: Analyze teachers' beliefs about the teaching culture regarding their pedagogical practice and teamwork among them. The study is qualitative, following the process of the phenomenological method. We worked with two categories of study: teaching practice and teamwork. To carry out the investigation, five secondary school teachers were considered as informants and, to collect the information, a semi-structured interview was conducted, which was applied in the same institution. According to the results, it was possible to analyze how the teaching culture is, recognizing the existence of subcultures within the same organization, which have attributed different meanings to what is the teaching practice and to teamwork.